THE DILEMMA OF NEOLIBERAL REFORMS IN POST-COVID-19 AFRICA - (:unkn) unknown (My University, 2022)
African countries started to accept neoliberal reforms since the 1980s and 1990s. Shaped by neoliberalism and marked by certain weaknesses, public health systems in Africa show certain limitations in responding to the COVID-19 pandemic. As a result, it is an imperative to bring the state back in. This research relies on the methods of document analysis and process tracing to find out the causes of neoliberal reforms. It appears that following an economic recession, many African countries, under financial pressure, have undertaken a new cycle of neoliberal reforms by accepting the conditionality of the International Monetary Fund (IMF) and the World Bank (WB). Post-COVID-19 African countries are faced with the dilemma due to the contradiction between the need for the return of the state with an important role and the necessity for the maintenance of neoliberalism. Nevertheless, they continue to pursue the neoliberal reforms that have long been criticized. China-Africa cooperation provides an alternative to the previous economic and health systems for African countries.
Keywords: African Research